NILAI-NILAI KEISLAMAN UNTUK MEMBENTUK KARAKTER SISWA - Rintia; Arista, Iswandi (Al-Iqro', 2024)
Education is a process of acculturation or "enculturation" a process so that a person is able to live in a certain culture. Therefore, education must be in accordance with the culture of society so as not to cause deviations from the values and norms that live in society. This research was conducted using qualitative methods. With the research techniques that the author chose, such as observation, interviews and document analysis. Based on the results of research conducted, it was found that DM Triguna High School had implemented local-based education through Islamic values. The instilling of these values can be seen from the routine of praying and tadarus every morning and the application of sanctions by reading the Koran for students who violate or are late.